2010
DOI: 10.1098/rsif.2010.0116
|View full text |Cite
|
Sign up to set email alerts
|

Bird migration flight altitudes studied by a network of operational weather radars

Abstract: A fully automated method for the detection and quantification of bird migration was developed for operational C-band weather radar, measuring bird density, speed and direction as a function of altitude. These weather radar bird observations have been validated with data from a high-accuracy dedicated bird radar, which was stationed in the measurement volume of weather radar sites in The Netherlands, Belgium and France for a full migration season during autumn 2007 and spring 2008. We show that weather radar ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
261
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(266 citation statements)
references
References 49 publications
4
261
0
1
Order By: Relevance
“…However, in most cases radar data are limited in duration to several minutes per bird, and nothing is known about the individuals tracked except their size. Thus, most radar studies have focused on large-scale timing and altitude of migration in response to changes in weather patterns (Richardson 1978, 1990, Kerlinger and Moore 1989, Bruderer et al 1995, Dokter et al 2010, Bridge et al 2011, La Sorte et al 2015. A few studies have tracked individuals up to several tens of minutes or even hours, but have not investigated altitude or changes in altitude per se (e.g., Gudmundsson 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, in most cases radar data are limited in duration to several minutes per bird, and nothing is known about the individuals tracked except their size. Thus, most radar studies have focused on large-scale timing and altitude of migration in response to changes in weather patterns (Richardson 1978, 1990, Kerlinger and Moore 1989, Bruderer et al 1995, Dokter et al 2010, Bridge et al 2011, La Sorte et al 2015. A few studies have tracked individuals up to several tens of minutes or even hours, but have not investigated altitude or changes in altitude per se (e.g., Gudmundsson 1994).…”
Section: Introductionmentioning
confidence: 99%
“…17 we find that Z e ¼ 15 dBZ translates to g ¼ 6.9 3 10 À11 /m. A more meaningful biological interpretation of g results if we express this quantity in units of square centimeters per cubic kilometer (cm 2 /km 3 ), a convention already used by some (e.g., Dokter et al 2011, ShamounBaranes et al 2011. That is, a value of Z e ¼ 15 dBZ as measured using NEXRAD corresponds to g ¼ 690 cm 2 /km 3 .…”
Section: Reflectivity As a Biological Parametermentioning
confidence: 99%
“…These values were motivated in part by the results shown in Fig. 3 of Dokter et al (2011). For reference, we show upper and lower bounds of the two-way beam pattern for NEXRAD (defined by the 3-dB points) that would result using a 0.58 elevation angle and assuming that the center of the box is located 50 km and 100 km from the radar.…”
Section: Effects Of Non-uniform Distribution Of Bioscattermentioning
confidence: 99%
“…Nocturnally migrating passerines have been recorded at a range of altitudes up to and over 5000 m (Liechti and Schaller 1999, Liechti and Schmaljohann 2007, Schmaljohann et al 2009), but in some instances a significant number of birds have been found to migrate in the lower altitudes, below 1500 m above ground level (agl; Able 2004, Mabee et al 2006, Longcore et al 2008, Schmaljohann et al 2008, Dokter et al 2011. Depending on site, this range of lower flight altitudes may occur in one season only (Schmaljohann et al 2009) or during both spring and fall movements (Bruderer 1997).…”
Section: Introductionmentioning
confidence: 99%